Technology that achieves the Triple Aim: an economic analysis of the BrainPathTM approach in neurosurgery - Norton SP; Dickerson EM; Kulwin CG; Shah MV (Dove Medical Press, 2017)
Sidney P Norton,1 Evan M Dickerson,1 Charles G Kulwin,2 Mitesh V Shah2 1Financial Planning and Analysis, Indiana University Health, Indianapolis, IN, USA; 2Adult Neurosurgery, Goodman Campbell Brain and Spine, Indianapolis, IN, USA Background: The Triple Aim is defined as: improving the patient experience of care, improving the health of populations, and reducing the per capita cost of health care. The purpose of this analysis was to evaluate the economic value of a new neurosurgical technique, the BrainPath™ approach, for use in patients with subcortical tumors and intracerebral hemorrhage (ICH). Methods: Inpatient length of stay (LOS) data were collected for ICH and brain tumor surgical patient cases between August 2013 and November 2015. Patient cases were separated into two groups; BrainPath approach (n = 28) and conventional techniques, such as craniotomy, (n = 208). The average intensive care unit (ICU) LOS was calculated for each group by diagnosis-related group and compared between groups. Results: The new surgical technology resulted in surgical intervention in 14 ICH cases which otherwise would have been medically managed due to the hemorrhage location or size of the ICH. A reduction in ICU LOS was seen in this group. Based on the variable direct cost per day in the neuro critical care unit at this academic medical center, 14 patient cases incurred ~ US$210,000 less in direct ICU costs. Surgical resection was possible in two tumor patient cases which would have been biopsied, rather than surgically resected, also due to location of the abnormalities. A total net value of > US$329,000 is attributable to the analyzed approach over a 28-month period. Conclusion: This analysis shows positive economic value for the new technology group when ICU LOS and reimbursement are considered against equipment costs, thus achieving Triple Aim objectives. Keywords: brain tumor, intracranial hemorrhage, intracerebral hemorrhage, intensive care unit length of stay, Triple Aim, economic value